Studi Deskriptif Kebahagiaan pada Mahasiswa Baru - Herdian Putra, Ade; Hariko, Rezki (JKI (Jurnal Konseling Indonesia), 2023)
Ideally freshmen can adjust to the academic demands of higher education. In addition, freshmen also need to adjust to life as a student university. The inability to adjust in the early days of being a student university has the potential to cause psychological conditions that are not conducive, so that freshmen tend to be at a low level of happiness. This condition if left unchecked can reduce academic achievement and ineffectiveness in living life. The purpose of this research is to describe the happiness of freshmen. This research involved 314 freshmen of the Faculty of Education, Universitas Negeri Padang (UNP) as respondents. The research instrument used is the Happiness Scale. Analysis of the research data used is quantitative descriptive analysis. The results of this study indicate that overall the average value of the happiness level of freshmen is 54.94 with an ideal score of 80. Furthermore, the percentage value of freshmen happiness is 68.67%. This shows that the happiness level of freshmen is in the high category. Furthermore, demographic data on the happiness level of freshmen shows that freshmen of the Guidance and Counseling Study Program are at the highest level of happiness compared to freshmen of other study programs at the Faculty of Education UNP, while the freshmen of the Teacher Education for Early Childhood Education Study Program is at the lowest level of happiness. University counseling centers have an important role in increasing the happiness of freshmen through proper counseling services.